M. Bulgakov in the assessment of G. Adamovich (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article analyzes the works of one of the biggest critics of the Russian emigration of the twentieth century G. Adamovich, dedicated to the early works of Mikhail Bulgakov. The critic points out the writer's skill, inherent historicism, satirical focus and a critical attitude towards reality.
Keywords: literature; criticism; story; novel; character; satire; historicism